The family-school partnership in most vulnerable students’ education (Journal of Parents and Teachers, 2012)
The purpose of this paper is to promote the reflection about the sense and importance of the construction of partnership between families and schools for developing and education of children. This analysis is placed in the inclusive education and aims this partnership as a strategic condition to increase inclusive education. Otherwise, it is claimed the attention about it in case of families with children vulnerable to exclusion processes. Finally, in this article are provided some keys for its construction based on a reflection process by families and professional teams.
Keywords: familiy-school partnership; inclusive education; school improvement; social vulnerability; experiencies